Linking landscape pattern and human disturbance on a regional level : a case study in Beira Interior region, Portugal - Quinta-Nova, L. C. (2022)
The land use and land cover pattern of landscapes are key elements of basic landscape structure; accordingly, his pattern has an important role in landscape management, nature conservation and preservation. In the other hand the human impact on the ecological environment has attracted a significant amount of attention. In this study, hemeroby index (HI) was used to quantify the degree of human disturbance, and the relationship between HI and landscape pattern metrics was explored in a region of Central Portugal. The main objectives of this study were to analyze the temporal and spatial characteristics of landscape pattern, and its relationship with different degrees of human disturbance. The Spearman’s correlations were determined to reveal the statistical connections between the landscape metric parameters and the HI values. At a landscape level the Mean Perimeter-Area Ratio (MPAR) showed a significant statistical connection with the HI. At a class level most of the metrics can be used to estimate the spatial changes of the hemeroby level, with Mean Patch Size (MPS) and Mean Perimeter-Area Ratio (MPAR) showing significant statistical connection with the hemeroby index, for agricultural areas, pastures and seminatural areas.